¿What does neuroeducation provide us for a better process – teaching – learning? - Fuentes Romero, Tiffany Kate (2018)
We propose to consider different aspects that also result important ones in human beings for a good process of teaching - learning. Actually, the new discipline called neuroeducation are nurturing us of a lot of contents which help to all teachers to comprehend these processes and regard on several situations of one person. We do not focus on education only in school even without contents which are proposed in class. Now, we must expand our vision in relation to the student, the social and familiar environment. What and how others factors are really involved with the student since our position as teachers, however, we are responsible and engaged to provide an integral and transversal education, that generate as an outcome: individuals of integrity, independence, intelligence, and with a high ability of solving problems.